What moves the German land market? A decomposition of the land rent-price ratio - Jana Plogmann; Oliver Mußhoff; Martin Odening; Matthias Ritter (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2018)
The price increases on agricultural land markets in the last decade have triggered a debate about land as an attractive investment opportunity for agricultural and non-agricultural investors. In a static environment, the rent-price ratio provides a first indicator of the profitability of an investment in land. In this paper, we apply the dynamic Gordon growth model to Western Germany and decompose the rent-price ratio into the expected present values of rental growth rates, real interest rates, and a land premium, i.e., the excess return on investment. This analysis reveals that the recent price surge on agricultural land markets was not unprecedented; that the land market rent-price ratio is rather low compared to other markets and varies considerably among federal states; and that (expected) premia for land are mostly negative, rendering investments in farmland unprofitable for financial investors. Finally, we find that changing expected present values of returns on land investments are the major driver for land price volatility.
Keywords: C32; G12; Q15; 330; Agricultural land market; rent-price ratio; Campbell-Shiller decomposition; dynamic Gordon growth model